Response of Taro to Varying Water Regimes and Soil Textures - Li, Meiling [UNESP]; Fernandes Deus, Angelica Cristina [UNESP]; Ming, Lin Chau [UNESP] (Asce-amer Soc Civil Engineers, 2019)
Taro [Colocasia esculenta (L.) Schott] is a major root crop widely distributed in the tropics and subtropics. However, little information is available on its water stress tolerance under different soil textures. Therefore, this study aimed to evaluate the effects of five water regimes (20%, 60%, 100%, 140%, and 180% ETc-crop water requirement) and three soil textures (clay, sandy clay loam, and sandy soil) on the growth, yield, and water-use efficiency (WUE) of taro. The experiment was conducted in a greenhouse, and two harvests of taro were analyzed. In both harvests, leaf number (LN), leaf area (LA), and corm yield (Yc) were lower at 20% and 60% ETc when compared with 100% ETc, and higher at 140% ETc and 180% ETc when compared with 100% ETc. Sandy soil (SS) exhibited higher LN at all water regimes than clay soil (CS) and sandy clay loam (SCL) soil. For LA, the values found in SS were higher at lower water regimes (20% and 60% ETc). In the three types of soil, WUE was significantly higher at 20% ETc, 1.00 and 0.51 kg m-3, respectively, in the first and second harvests compared with the other water regimes. In the second harvest, WUE and Yc were significantly higher in SS compared with CS and SCL, indicating that SS has greater potential to improve the WUE of taro under limited water availability conditions.
Keywords: Irrigation; Soil type; Corm yield; Canopy size; Water-use efficiency (WUE)